Boron-containing D–A–A type TADF materials with tiny singlet–triplet energy splittings and high photoluminescence quantum yields for highly efficient OLEDs with low efficiency roll-offs. Issue 11 (19th February 2020) - Qu, Cheng; Xia, Guoqi; Xu, Yincai; Zhu, Yunlong; Liang, Jixiong; Zhang, Hao; Wang, Jiaxuan; Zhang, Zuolun; Wang, Yue
Abstract : D–A–A type TADF materials possessing concurrently a small Δ E ST and a high Φ PL for efficient OLEDs were constructed by utilizing boryl-containing tandem acceptors. Abstract : Thermally activated delayed fluorescence (TADF) emitters have great potential for use in commercial organic light-emitting diode (OLED) displays/lighting. One of the usually confronted issues of TADF emitters is that short triplet-exciton lifetimes and a high photoluminescence quantum yield ( Φ PL ) are hard to achieve simultaneously. In this study, by integrating a bismesitylboryl acceptor with a triazine/sulfonyl acceptor, tandem acceptors were assembled and utilized to construct two donor–acceptor–acceptor (D–A–A) types of TADF compounds. These compounds show a very small singlet–triplet energy splitting (Δ E ST : < 0.04 eV), which results in fast deactivation of triplet excitons via reverse intersystem crossing (RISC) and, correspondingly, a fairly short delayed-fluorescence lifetime ( τ DF : <4 μs in doped films). Meanwhile, high Φ PL values of 65 and 84% were maintained by the compounds. The short Δ E ST is contributed by the large HOMO–LUMO spatial separation caused by the expanded LUMO distribution that is due to the unique p–π* conjugation between boron and the other parts of the tandem acceptor. Benefiting from the small Δ E ST and high Φ PL, OLED devices based on these emitters showed a maximum external quantum efficiency reaching 24.8% and a very low efficiency roll-off of 5.6% at a practical luminance of 1000 cd m −2 . This study indicates that expanding the acceptor unit of the D–A type of TADF materials through introducing the empty p-orbital of boron is an effective strategy for the development of TADF materials towards high-performance OLEDs.